2020
DOI: 10.1002/pro.3960
|View full text |Cite
|
Sign up to set email alerts
|

Cryo‐electron microscopy structure of human ABCB6 transporter

Abstract: Human ATP-binding cassette transporter 6 of subfamily B (ABCB6) is an ABC transporter involved in the translocation toxic metals and anti-cancer drugs. Using cryo-electron microscopy, we determined the molecular structure of full-length ABCB6 in an apo state. The structure of ABCB6 unravels the architecture of a full-length ABCB transporter that harbors two N-terminal transmembrane domains which is indispensable for its ATPase activity in our in vitro assay. A slit-like substrate binding pocket of ABCB6 may ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 48 publications
0
27
1
Order By: Relevance
“…The molecular mechanisms of transmembrane transportation and substrate recognition for ABCB6 remain unclear, as well as the mechanism underlying pathogenic mutations and drug resistance. Recently, Wang et al 23 reported the cryo-EM structure of human ABCB6 and provided a structural glimpse of this transporter. However, this study mainly bases on a 4.0-Å resolution model, which is borderline sufficient to identify side chains.…”
Section: Introductionmentioning
confidence: 99%
“…The molecular mechanisms of transmembrane transportation and substrate recognition for ABCB6 remain unclear, as well as the mechanism underlying pathogenic mutations and drug resistance. Recently, Wang et al 23 reported the cryo-EM structure of human ABCB6 and provided a structural glimpse of this transporter. However, this study mainly bases on a 4.0-Å resolution model, which is borderline sufficient to identify side chains.…”
Section: Introductionmentioning
confidence: 99%
“…The other well-resolved segment of the R region is located on the peripheral face of NBD1, opposite the ATP binding and NBD dimerization interfaces (Fig. 3A, right (9,10,(12)(13)(14).…”
Section: Regulatory (R) Region Interactions Explain Its Regulatory Rolementioning
confidence: 99%
“…A TMD0, but not L0 linker, is also found in some ABCB proteins (3,5). These Nterminal extensions are involved in trafficking, endosomal recycling, protein interactions, and/or regulation of ABC activity (9)(10)(11)(12)(13)(14)(15)(16)(17)(18). The existence of disease-causing mutations in TMD0 and L0 linker of different ABCC proteins (8,13,18) indicates that TMD0 and the L0 linker play important roles in protein function when present.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations